Economic burden of incident interstitial lung disease (ILD) and the impact of comorbidity on costs of care - Frank, Anna Lena; Kreuter, Michael; Schwarzkopf, Larissa (Respiratory medicine, 2019)
Introduction - Evidence about the economic burden related to interstitial lung diseases (ILDs) and the cost-driving factors is sparse. In the knowledge that distinct comorbidities affect the clinical course of ILDs, our study investigates their impact on costs of care within first year after diagnosis. - Methods - Using claims data of individuals diagnosed with Idiopathic Interstitial Pneumonia (IIP) (n=14453) or sarcoidosis (n=9106) between 2010 and 2013, we calculated total and ILD-associated mean annual per capita costs adjusted by age, sex and comorbidity burden via Generalized Linear Gamma models. Then, we assessed the cost impact of chronic obstructive pulmonary disease (COPD), diabetes, coronary artery disease, depression, gastro-esophageal reflux disease, pulmonary hypertension (PH), obstructive sleep apnoea syndrome (OSAS) and lung cancer using the model-based parameter estimates. - Results - Total mean annual per capita costs were €11 131 in the pooled cohort, €12 111 in IIP and €8793 in sarcoidosis, each with a 1/3 share of ILD-associated cost. Most comorbidities had a significant cost-driving effect, which was most pronounced for lung cancer in total (1.989 pooled, 2.491 sarcoidosis, 1.696 IIP) and for PH in ILD-associated costs (2.606 pooled, 2.347 IIP, 3.648 sarcoidosis). The lung-associated comorbidities COPD, PH, OSAS more strongly affected ILD-associated than total costs. - Conclusion - Comorbidities increase the already substantial costs of care in ILDs. To support patient-centred ILD care, not only highly cost-driving conditions that are inherent with high mortality themselves require systematic management. Moreover, conditions that are more rather restricting the patient's activities of daily living should be addressed - despite a low-cost impact.
Gesehen am 23.09.2019